Learning Based On Information Technology and Learning Strategy Communication in Facing Industrial Revolution Era 4.0 - Warih Bimayu; Nopriadi Nopriadi (Universitas Bengkulu, 2019)
The educational world in Indonesia experiences a phenomenon in the face of the era of industrial revolution 4.0, this can have a significant impact on the world of education. Many scientists, experts, organizations, educational institutions, universities make strategies in facing the era of industrial revolution 4.0. One of them conducted by the Federation of Information and Communication Technology Teachers) held a workshop in Jakarta, 6-7 October 2018 themed